Digital branding : a complete step-by-step guide to strategy, tactics and measurement - Rowles, Daniel (Kogan Page, 2014)
" In a fast changing environment where social media has a heavy impact on marketing and branding efforts, Digital Branding provides guidance on creating, implementing and measuring digital campaign strategies. Daniel Rowles presents a step-by-step, practical framework for brand planning, channel selection and measuring the effectiveness of brand campaigns. Exploring topics like content marketing, social media, search optimization and web analytics, Digital Branding contains real world case studies, a guide to free and paid tools to help measure the ROI from various online channels, and examples of social guidelines, process and policy"--Resumé vydavatele
Keywords: internetový marketing; řízení značky; obchodní značky; Internet marketing; brand management; brand name products; příručky; handbooks, manuals, etc